La estrategia competitiva como mediadora del efecto de la orientación empresarial en el rendimiento de la empresa: un estudio de pymes registradas seleccionadas en el estado de Ilorin kwara - Oluwayomi Omotayo, Olota (Pontificia Universidad Católica del Perú, 2025)
The ability of SMEs to sustain their performance amid market competition is deeply intertwined with their capacity to adopt and implement innovative business strategies. Hence, this paper aims to investigate competitive strategy as a mediator of the effect of entrepreneurial orientation on firm performance by conducting a study of selected registered SMEs in Ilorin Kwara State. Specifically, it examined the effect of innovativeness, proactiveness, and autonomy on firm performance and competitive strategy as a mediator. A descriptive survey research design was adopted with a population of 1,416 registered SMEs in Kwara State. A sample of 312 SMEs was administered a structured questionnaire. The data collected were analyzed using PLS-SEM. The findings revealed that autonomy has the strongest effect on firm performance (β = 0.401, t = 8.846, p < 0.000), followed by proactiveness (β = 0.219, t = 3.869, p < 0.000), and innovativeness (β = 0.137, t = 2.240, p = 0.026), while competitive strategy has the highest partial mediating effect on the innovativeness-performance relationship (VAF = 52%) followed by the proactiveness-performance relationship (VAF = 24%), but the autonomy-performance relationship (VAF = 8%) has no significant mediating effect. The study concludes that competitive strategy as a mediator is significantly vital for the effect of entrepreneurial orientation on firm performance in selected registered SMEs. Therefore, it is strongly recommended that, to strengthen the firm performance of SMEs, owners should consider competitive strategy in the form of a differentiation strategy and focus strategy, which help to enhance the contribution of entrepreneurial orientation to firm performance as they have a substantial influence on the relationship between entrepreneurial orientation and firm performance.

La capacidad de las PYME para mantener su rendimiento en un mercado competitivo está estrechamente relacionada con su capacidad para adoptar e implementar estrategias empresariales innovadoras. Por ello, este estudio examina la estrategia competitiva como mediadora del efecto de la orientación empresarial en el rendimiento empresarial: un estudio de las PYME seleccionadas registradas en el estado de Ilorin Kwara. Específicamente, se examinó el efecto de la innovación, la proactividad y la autonomía sobre el rendimiento empresarial, así como el papel de la estrategia competitiva como variable mediadora. Se adoptó un diseño de investigación descriptivo de encuesta con una población de 1 416 PYME registradas en el estado de Kwara. Se administró un cuestionario estructurado a una muestra de 312 PYME. Los datos recopilados se analizaron mediante PLS-SEM. Los hallazgos revelaron que la autonomía tiene el efecto más fuerte sobre el rendimiento empresarial (β = 0,401, t = 8,846, p < 0,000), seguida por la proactividad (β = 0,219, t = 3,869, p < 0,000) y, posteriormente, la innovación (β = 0,137, t = 2,240, p = 0,026). En cuanto al papel mediador de la estrategia competitiva, se observó un efecto mediador parcial más fuerte en la relación entre innovación y rendimiento empresarial (VAF = 52%), seguido por la relación entre proactividad y rendimiento (VAF = 24%). Sin embargo, no se identificó un efecto mediador importante en la relación entre autonomía y rendimiento (VAF = 8%). El estudio concluye que la estrategia competitiva desempeña un papel mediador significativamente relevante en la relación entre la orientación empresarial y el rendimiento empresarial de las PYME seleccionadas registradas. En consecuencia, se recomienda firmemente que, para fortalecer el rendimiento de estas empresas, sus propietarios consideren la adopción de estrategias competitivas, particularmente de diferenciación y enfoque, ya que estas potencian el impacto de la orientación empresarial sobre el rendimiento empresarial.
Competitive strategy as a mediator of the effect of entrepreneurial orientation on firm performance: a study of selected registered SMES in Ilorin Kwara state
Keywords: Competitive strategy; Entrepreneurial orientation; Firm performance; Innovativeness; Proactiveness; Estrategia competitiva; Orientación empresarial; Rendimiento empresarial; Innovación; Proactividad; https://purl.org/pe-repo/ocde/ford#5.02.04